The Phenomenon of Palestinian Runaway Girls and Its Relationship to Family Climate (Disintegration, Violence, and Impact of Friends): A Field Study in the Social Welfare Offices in Jerusalem - Khaled Salman; Khalid Hreish; Najwa Alsafadi (My University, 2015)
The study aims at identifying the phenomenon of Palestinian runaway girls and its relationship to family climate, a field study in the social welfare offices in Jerusalem. The study sample consists of (58) runaway girls of those officially registered in the social affairs offices in Jerusalem for the year (2014), age (13-22) years old. The study shows that there are no differences in domestic violence, family disintegration, and the impact of friends by age when girls run away. The results also indicate that there are differences in the impact of friends on the runaway girls by the place of stay after escape; there are differences in family disintegration of the runaway girls by the direct reason of escape. Furthermore, it is observed that there is no relationship between family disintegration of the runaway girls and the impact of friends; there is a relationship between family disintegration of the runaway girls and domestic violence; there is a relationship between the impact of friends and domestic violence.

هدفت الدراسة إلى التعرف الى ظاهرة هروب الفتيات الفلسطينيّات من منازل أسرهن وعلاقتها بالمناخ الاسري، دراسة ميدانيّة في مكاتب الرفاه الاجتماعيّ بالقدس. وتكونت عيّنة الدراسة من (58) فتاة هاربة من المسجلين في مكاتب الشؤون الاجتماعية بالقدس للعام )2014(، من المرحلة العمرية (13-22). وأظهرت النتائج أنّه لا توجد فروق في العُنف الأسريّ، والتفكك الأسريّ، وتأثير الرفاق تعزى لمتغير العمر عند هروبها من المنزل، بينما توجد فروق في تأثير الرفاق على الفتاة الهاربة تعزى لمتغير مكان اللجوء بعد هروبها من المنزل، وتوجد فروق في التفكك الأسريّ للفتاة الهاربة تعزى لمتغير سبب هروبها من المنزل. كما وأظهرت النتائج أنّه لا توجد علاقة بين التفكك الأسريّ للفتاة الهاربة وبين تأثير الرفاق، بينما توجد علاقة بين التفكك الأسريّ للفتاة الهاربة والعُنف الأسريّ، اي ان كلما كان تفكك اسري داخل الاسرة ازداد العنف الاسري بداخلها. وتوجد علاقة طردية بين مستوى تأثير الرفاق، وبين مستوى العُنف الأسريّ، اي ان كلما زاد تأثير الرفاق على الفتاة كلما زاد تعرضها للعنف داخل البيت.
ظاهرة هروب الفتيات الفلسطينيّات من منازل أسرهن وعلاقته بالمناخ الأسريّ: (التفكك، والعنف، وتأثير الرفاق)، دراسة ميدانيّة في مكاتب الرفاه الاجتماعيّ بالقدس